Upaya Pemenuhan Dokter Spesialis Berstatus Aparatur Sipil Negara Di Rumah Sakit Umum Daerah Ditinjau Dari Undang-Undang Nomor 44 Tahun 2009 Tentang Rumah Sakit - Evan Prasetianto (Lembaga Pengembangan Kinerja Dosen, 2023)
Human resources referred to are the provision of resources both in terms of quantity and quality of medical personnel and health workers. So far, it can be easily found that the local government has difficulty in fulfilling these personnel, especially specialist doctors. In several years, the formation of civil servants with the formation of medical specialists did not register. This is of course the obligation of the government, both the central and regional governments, to provide these resources so that not only can the hospital be built, but the human resource aspect cannot be fulfilled.